Comparison between the tectonic movements of Nanga Parbat-Haramosh Massif and Mt. Everest - Poretti, Giorgio; Calligaris, Chiara; Tariq, Shahina; Khan, Hawas (Journal of Nepal Geological Society, 2011)
Available with full text.